Lung carcinoma paraneoplastic reactive regional pericarditis mimicking ST elevation myocardial infarct - Yadav Bijay; Varun Miriyala; Sadip Pant; Ravi Chander; Javed Nosheen; Keith D. Turcotte; Sophia Rizk; Nick Mucciardi; Kaplan Randy; Shanjin Cao (Greater Baltimore Medical Center, 2021)
ST-elevation myocardial infarction (STEMI) is a cardiac emergency. However, multiple clinical disorders can cause ST-elevation ECG changes, one of which is pericarditis. Regional pericarditis is a less known clinical phenomenon that can mimic STEMI. We report a case of poorly differentiated lung carcinoma associated reactive regional pericarditis mimicking inferior STEMI.